2013
DOI: 10.5539/ibr.v6n10p153
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macroeconomic Variables and Banks Characteristics on Jordanian Islamic Banks Profitability: Empirical Evidence

Abstract: The aim of this study is to determine the effect of macroeconomic Variables (external variables) and bank characteristic (internal variables) on the profitability of Jordanian Islamic banks for the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011).the study used panel data analysis fixed effects model and the generalized least square method to examine the study hypotheses. The empirical analysis shows that capital adequacy, bank size have a positive and significant impact on retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
2
15
0
2
Order By: Relevance
“…This finding is consistent with monetary theory, whereby as countries move from monetary targeting to inflation targeting, the interest channel of monetary policy becomes more effective relative to the other channels [6]. Our study results in this respect is inconsistent with the results of [51] who showed that in Jordanian Banks, the effect of growth of money supply on Return on Assets was positive and significant.…”
Section: Discussion Of Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This finding is consistent with monetary theory, whereby as countries move from monetary targeting to inflation targeting, the interest channel of monetary policy becomes more effective relative to the other channels [6]. Our study results in this respect is inconsistent with the results of [51] who showed that in Jordanian Banks, the effect of growth of money supply on Return on Assets was positive and significant.…”
Section: Discussion Of Resultssupporting
confidence: 56%
“…Money Supply and bank profitability: A study by [51] on Jordanian Islamic Banks with Return on Assets (ROA) as measures of profitability found that growth in money supply had a positive effect on the profitability of banks. [52] conducted a study on the main determinants of performance for commercial banks in Japan covering the period of the global financial crisis and adopted Net interest income as a measure of performance.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…(4), a wellcapitalized bank needs to borrow less to support a given level of assets. (5), PLS principle allows the Sharia bank to make additional financing with beneficial return which should imply higher profitability, [3,[36][37][38][39][40][41]. Capital is the most important factor for Sharia banking, strong capital shows the stability and resilience of banks in the face of risks and uncertainties in investment in the banking sector [42].The results of the study found that capital adequacy negatively affects the profitability, these findings indicate that the level of capitalization of banks is inadequate, Sharia banks have not maximized capital in their operationalization, most of the financing activities in Sharia Bank is not covered by capital, so that financing activities have high risk that affects profitability, thus Sharia banks need to maximize and improve capital, which means lowering capitalization leads to decrease in profitability.…”
Section: Discussionmentioning
confidence: 99%
“…It can be defined according to Guru et al, (2002) as an external source of business finance that a firm can use to improve its financial position and performance. For the Jordanian Islamic Banks, Qudah and Jaradat (2013) find that there is a negative and insignificant relationship between profitability and leverage. Izhar and Asutaya (2007) also established a negative and significant relationship between leverage and profitability in one Indonesian Islamic bank.…”
Section: Leveragementioning
confidence: 95%